Real-Time Indonesian Language Speech Recognition with MFCC Algorithms and Python-Based SVM - Wening Mustikarini; Risanuri Hidayat; Agus Bejo (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
Abstract — Automatic Speech Recognition (ASR) is a technology that uses machines to process and recognize human voice. One way to increase recognition rate is to use a model of language you want to recognize. In this paper, a speech recognition application is introduced to recognize words